Correlation between HbA1C and Infarct Volume in Acute Ischemic Stroke - Mirawati, Diah Kurnia; Riany, Navidya Ade; Subandi, Subandi; Hamidi, Baarid Luqman; Rahayu, Rachmi Fauziyah; Budianto, Pepi; Hafizhan, Muhammad; Putra, Stefanus Erdana (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Stroke is second leading cause of death worldwide. Chronic hyperglycemia can promote neuronal toxicity. The previous study shows that acute hyperglycemia is correlated with infarct volume of ischemic stroke. AIM: This study aims to investigate the correlation between hemoglobin A1C (HbA1C) and infarct volume on acute ischemic stroke. METHODS: This is a cross-sectional study in acute ischemic stroke patient in Dr. Moewardi General Hospital, Surakarta, Indonesia. Data of infarct volume were collected from head computed tomography (CT)-scan and calculated with A × B × C/2 formula. We also collected lipid and patients’ glycemic profile from patients’ blood laboratory result. Head CT-scan and laboratory data of participants analyzed with Pearson and Spearman’s rho test for parametric and non-parametric data, respectively. We also performed multivariate analysis to evaluate confounding covariates. p < 0.05 was considered as statistically significant. RESULTS: A total of 38 participants were included in this study, with mean infarct volume was 0.46 ± 0.64cc and mean HbA1C was 6.96 ± 2.69%. Bivariate analysis shows strong positive correlation between infarct volume and HbA1C with r = 0.898 (p < 0.001). Other variable that showed a significant correlation with infarct volume were diabetes mellitus history (r = 0.671; p < 0.001), random blood su gar (r = 0.466; p = 0.003), fasting blood sugar (r = 0.636; p < 0.001), 2-h postprandial glucose level (r = 0.646; p ≤ 0.001), high density lipoprotein (r = −0.354; p = 0.029), and triglyceride (r = 0.429; p = 0.007). Based on multivariate analysis, HbA1C regression coefficient on infarct volume was B = 0.222 (p < 0.001), indicating that HbA1C as one of the variables contributing to volume of infarct. CONCLUSIONS: There is a strong positive correlation between infarct volume and HbA1C, and HbA1C is variable contribute to the volume of infarct.